2017
DOI: 10.1186/s12935-017-0404-z
|View full text |Cite
|
Sign up to set email alerts
|

HLBT-100: a highly potent anti-cancer flavanone from Tillandsia recurvata (L.) L.

Abstract: BackgroundThe incidence and mortalities from cancers remain on the rise worldwide. Despite significant efforts to discover and develop novel anticancer agents, many cancers remain in the unmet need category. As such, efforts to discover and develop new and more effective and less toxic agents against cancer remain a top global priority. Our drug discovery approach is natural products based with a focus on plants. Tillandsia recurvata (L.) L. is one of the plants selected by our research team for further studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 74 publications
0
13
0
1
Order By: Relevance
“…WST assay has also been used frequently as a cell viability assay. Lowe, Toyang, Watson, Ayeah, and Bryant () have utilized WST assay to assess cytotoxic effects of a flavonoid (HLBT‐100) in brain (U87 MG), breast (MDA‐MB‐231), melanoma (A375), leukemia (MV4‐11) and prostate (PC‐3) cancer cell lines. An in vitro study conducted by Chen et al () demonstrated cytotoxic effects of hinokitiol in breast cancer stem/progenitor cells using the WST assay.…”
Section: Cell Viability/cytotoxicity and Antiproliferative Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…WST assay has also been used frequently as a cell viability assay. Lowe, Toyang, Watson, Ayeah, and Bryant () have utilized WST assay to assess cytotoxic effects of a flavonoid (HLBT‐100) in brain (U87 MG), breast (MDA‐MB‐231), melanoma (A375), leukemia (MV4‐11) and prostate (PC‐3) cancer cell lines. An in vitro study conducted by Chen et al () demonstrated cytotoxic effects of hinokitiol in breast cancer stem/progenitor cells using the WST assay.…”
Section: Cell Viability/cytotoxicity and Antiproliferative Assaysmentioning
confidence: 99%
“…WST assay has also been used frequently as a cell viability assay. Lowe, Toyang, Watson, Ayeah, and Bryant (2017) have utilized WST assay to assess cytotoxic effects of a flavonoid (HLBT-100) in brain (U87 MG), breast (MDA-MB-231), melanoma (A375), leukemia (MV4-11) and prostate (PC-3) cancer cell…”
Section: Introductionmentioning
confidence: 99%
“…7 On the other hand, these phenolic compounds have showed wide range of pharmacological activities including antioxidant, 8 anti-inflammatory, 9 antimicrobial, 10,11 antihemorragic activities 12 and anticancer activity. 13 In recent years, the study of the flavonoids took a great place in research studies due to the improvement of the extractive techniques and the progress of the methods of structural analysis. Hence, the present study intended to identify the flavonoids isolated from flowers and their distribution in different horticultural types of Begonia.…”
Section: Introductionmentioning
confidence: 99%
“…The Bromeliaceae family is composed of 58 genera and 3,408 species native to America distributed from Argentina to the southern United States (Benzing 2000, Luther 2014). Some species have important pharmacological activities, such as anthelmintic (Stepek et al 2005), antinociceptive (de Lima-Saraiva et al 2014), gastroprotective (Machado et al 2013), photoprotective (de Oliveira-Júnior et al 2017), anticancer (Lowe et al 2017), hypoglycemic (Witherup et al 1995) and antibacterial (Faller et al 2017) activity.…”
mentioning
confidence: 99%